2015
DOI: 10.1007/s10549-015-3609-7
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor promotes tamoxifen agonist activity by activation of EGFR in ERα-positive breast cancer

Abstract: Purpose Tamoxifen (Tam) resistance represents a significant clinical problem in estrogen receptor (ER) -positive breast cancer. We previously showed that decreased expression of Rho guanine nucleotide dissociation inhibitor (Rho GDI), a negative regulator of the Rho GTPase pathway, is associated with Tam resistance. We now discover that androgen receptor (AR) is overexpressed in cells with decreased Rho GDI and seek to determine AR’s contribution to resistance. Methods We engineered ER -positive cell lines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 37 publications
4
46
1
Order By: Relevance
“…However, AR has also been reported to contribute to therapy resistance in ER+ breast cancer cells overexpressing AR, with increase in AR-to-ESR1 ratio associated with worse outcome for tamoxifen-treated patients (Cochrane et al 2014) and increased agonist activity of Tam in AR overexpressing cells. In this context, AR reportedly increased tamoxifen agonist activity via the activation of EGFR in ER+ breast cancer, and this was blocked by dual treatment with the anti-androgen enzalutamide and EGFR inhibitor gefitinib (Ciupek et al 2015). In addition, AR appears to promote proliferation of molecular apocrine breast cancer; a subset of TNBC expressing AR, through activation of genes that are normally regulated by ESR1 in ER+ cancer (Robinson et al 2011).…”
Section: Nr Expression In Breast Cancer Subtypesmentioning
confidence: 99%
“…However, AR has also been reported to contribute to therapy resistance in ER+ breast cancer cells overexpressing AR, with increase in AR-to-ESR1 ratio associated with worse outcome for tamoxifen-treated patients (Cochrane et al 2014) and increased agonist activity of Tam in AR overexpressing cells. In this context, AR reportedly increased tamoxifen agonist activity via the activation of EGFR in ER+ breast cancer, and this was blocked by dual treatment with the anti-androgen enzalutamide and EGFR inhibitor gefitinib (Ciupek et al 2015). In addition, AR appears to promote proliferation of molecular apocrine breast cancer; a subset of TNBC expressing AR, through activation of genes that are normally regulated by ESR1 in ER+ cancer (Robinson et al 2011).…”
Section: Nr Expression In Breast Cancer Subtypesmentioning
confidence: 99%
“…Moreover, increased AR expression has been observed in TAM-resistant breast cancer models in vitro and in vivo [126,127]. In fact, it has recently been reported that TAM-resistant tumors express higher levels of AR than TAM-sensitive tumors.…”
Section: Tam Resistancementioning
confidence: 99%
“…Our one HER2+ER− PDX line is AR+ and, where measured, 2/6 TN PDX lines are AR+ (Figure 1D). Each of these types of PDX models will be valuable as AR is being investigated as a putative target in ER+ and ER− tumor subtypes [6365]. Unlike ER and PR which reside predominantly in the nucleus in both the absence or presence of ligand, AR is usually cytoplasmic and is shuttled to the nucleus with addition of an androgenic ligand.…”
Section: Methodological Considerationsmentioning
confidence: 99%